Utilizing liquid-liquid biopolymer regulators to predict the prognosis and drug sensitivity of hepatocellular carcinoma - Jianhao Li; Han Chen; Lang Bai; Hong Tang (Biology Direct)
Abstract Background Liquid-liquid phase separation (LLPS) is essential for the formation of membraneless organelles and significantly influences cellular compartmentalization, chromatin remodeling, and gene regulation. Previous research has highlighted the critical function of liquid-liquid biopolymers in the development of hepatocellular carcinoma (HCC). Methods This study conducted a comprehensive review of 3,685 liquid-liquid biopolymer regulators, leading to the development of a LLPS related Prognostic Risk Score (LPRS) for HCC through bootstrap-based univariate Cox, Random Survival Forest (RSF), and LASSO analyses. A prognostic nomogram for HCC patients was developed using LPRS and other clinicopathological factors. We utilized SurvSHAP to identify key genes within the LPRS influencing HCC prognosis. To validate our findings, we collected 49 HCC cases along with adjacent tissue samples and confirmed the correlation between DCAF13 expression and HCC progression through qRT-PCR analysis and in vitro experiments. Results LPRS was established with 8 LLPS-related genes (TXN, CBX2, DCAF13, SLC2A1, KPNA2, FTCD, MAPT, and SAC3D1). Further research indicated that a high LPRS is closely associated with vascular invasion, histological grade (G3-G4), and TNM stage (III-IV) in HCC, concurrently establishing LPRS as an independent risk factor for prognosis. A nomogram that integrates LPRS with TNM staging and patient age markedly improves the predictive accuracy of survival outcomes for HCC patients. Our findings suggest that increased DCAF13 expression in HCC plays a crucial role in cancer progression and angiogenesis. Navitoclax has emerged as a promising treatment for HCC patients with high LPRS levels, offering a novel therapeutic direction by targeting LLPS. Conclusion We have formulated a novel LPRS model that is capable of accurately predicting the clinical prognosis and drug sensitivity of HCC. DCAF13 might play a pivotal role in malignant progression mediated by LLPS.